MODAL DALAM NOVEL THE HOBBIT, OR THERE AND BACK AGAIN KARYA J.R.R TOLKIEN - Mentang, Richard Eduard (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT In English there are two subclasses of verbs, those are lexical verb and auxiliary verb. Modals are a class of auxiliary verbs that are combined with the basic form to make verb phrase with a wide meaning. This study is an attempt to describe and analyze the modals in the novel â€œThe Hobbit or There and Back Againâ€ by J.R.R Tolkien. The aim of this research is to identify and classify the form and meanings of modals. The method used in this research is descriptive method. The data of modals have been taken from the sentences in the novel â€œThe Hobbit, or There and Back Againâ€ and analyzed by using Azarâ€™s concept. The result of this study shows that modal forms which are used namely can, could, will, might, must, should, and would, ought to, shall, may, and had better are not found in the novel â€œThe Hobbit or There and Back Againâ€. Modal form that are mostly used in this novel is â€œwouldâ€. This study can be continually done by analyzing modals in other literary works by using the concept of Azar. Keywords: Modals, English, Novel â€œThe Hobbit, or There and Back Againâ€